DEVELOPMENT OF LEARNING MEDIA ON VOLLEYBALL UNDER PASSING TECHNIQUES USING E-MODULE MEDIA FOR CLASS VII JUNIOR HIGH SCHOOL STUDENTS - agung, Agung Fitra Wanda (Universitas Negeri Medan, 2024)
This research is motivated by the fact that many volleyball underpassing lessons in schools are still conventional, as school learning activities are still teacher-centered. The objectives of this research are: To determine the feasibility of the Volleyball Bottom Passing E-Module Learning Media for junior high school students. This research uses a research and development model (Borg And Gall) using the ADDIE development model which includes (1) Research and Information Collecting (Preliminary Study), (2) Planning (Research Planning), (3) Develop Preliminary Form Of Product (Development Design), (4) Preliminary Field Testing (Preliminary/Limited Field Trial), (5) Main Product Revision (Main Product Revision/Limited Field Test Results) (6) Main Field Testing (Wider Product Trial) After media This learning was used in the implementation stage, learning media was declared suitable for use as teaching material in schools with an average material expert score of 3.7 and an average media expert score of 3.7, an average score of small group trials. amounted to 3.5 and students' response as users was 3.4 so the suitability of the learning media developed was in the